Association between neonatal birthweight and risk of maternal glucose intolerance after gestational diabetes mellitus - Li, Zhuyu; Wang, Dongyu; Cheng, Yunjiu; Chen, Peisong; Ding, Wenjing; Wang, Zilian (Journal of diabetes investigation, 2021)
Aims/Introduction To evaluate whether the neonatal birthweight (NBW) is associated with early postpartum glucose intolerance in women with gestational diabetes mellitus. Materials and Methods A total of 1,113 women diagnosed with gestational diabetes mellitus who completed an oral glucose tolerance test at 6–9 weeks postpartum between 1 April 2014 and 8 January 2020 were included in this observational prospective cohort study. They were grouped by neonatal birthweight quartiles, and the odds ratios of postpartum glucose intolerance for different levels of neonatal birthweight were assessed. Results A lower NBW quartile was associated with an increased maternal risk of postpartum glucose intolerance after gestational diabetes mellitus. The adjusted odds ratios for maternal glucose intolerance were 1.69 (95% confidence interval 1.13–2.51) in the lowest NBW quartile (NBW 1,980–2,930 g) when compared with the highest NBW quartile (NBW 3,410–4,610 g). The association between lower NBW and maternal glucose intolerance was significantly stronger in women who delivered a girl. Additionally, NBW ≥3,100 g appears to be associated with a lower risk of maternal glucose intolerance postpartum. Conclusions Our findings suggest that low NBW is a previously unrecognized risk factor for maternal glucose intolerance after gestational diabetes in early postpartum in South China. The present cohort study showed there were significantly inverse, graded associations between neonatal birthweight and the risk of maternal postpartum glucose intolerance after gestational diabetes mellitus. This study is the first to our knowledge to provide evidence that lower neonatal birthweight is a risk factor for early postpartum glucose disturbance after gestational diabetes mellitus.